Medicinal plants and folk uses in Trás-os-Montes (Portugal). An overview of phytochemical properties and bioactive compounds potential - Carvalho, Ana Maria (2011)
Ethnobotanical surveys conducted in north-eastern Portugal reported plant knowledge and uses of several wild species in folk medicine based on field studies using ethnographic methodologies. Taking advantage of a multidisciplinary team, besides botanical inventories and sociocultural and anthropological studies, we set out applied phytochemical research on locally used medicinal plants (more frequently cited, i.e. frequency of citation > 50%) that have special cultural significance. Experimental phytochemical research points to pharmacological effects that confirm the importance of the empirical use of these species and their contribution to a good health condition.